2022
DOI: 10.3390/su14148282
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Purchasing Determinants Towards Mountain Food Products

Abstract: Mountain agriculture is a very important source of ecosystem services, such as cultural heritage, traditional knowledge, and biodiversity. However, traditional farming practices in those areas, particularly dairy livestock, are in sharp decline. For this reason, it is fundamental to find a way to improve sustainability using a holistic approach as indicated by the European Green Deal and Farm to Fork strategies. The “Mountain product” label can be a suitable tool to reach this aim. However, studies on consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
(62 reference statements)
3
5
0
Order By: Relevance
“…Income represents the strongest predictor towards the quality signal evaluated in this paper, confirming previous studies that found a positive association among income, functional food, and functional claims used to communicate foods physiological effects [59,87]. The lack of link between income and a mountain label has not been found previously [4,41], and our result suggests that income is an important factor for this label, confirming the results of Bassi et al ( 2021) [38], with wealthier consumers willing to pay more for this claim.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Income represents the strongest predictor towards the quality signal evaluated in this paper, confirming previous studies that found a positive association among income, functional food, and functional claims used to communicate foods physiological effects [59,87]. The lack of link between income and a mountain label has not been found previously [4,41], and our result suggests that income is an important factor for this label, confirming the results of Bassi et al ( 2021) [38], with wealthier consumers willing to pay more for this claim.…”
Section: Discussionsupporting
confidence: 90%
“…Research has shown that the label can contribute to the support of local economies in mountainous areas [12,39,40]. Indeed, a positive relation has been found between WTP for mountain milk with older consumers and environmental friendliness [41]. Moreover, Mazzocchi and Sali, (2022) [12] found that mountain products can be perceived as carrying positive values, generating a higher WTP than organic products, but lower WTP than some animal welfare claims, using a choice experiment.…”
Section: Consumers' Behaviour Toward Mountain Labelled Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can allow consumers to better understand, how to translate their ecological concerns into meat consumption. Furthermore, in previous studies, it has been reported that the consumer's highest willingness to pay is associated with the EU Mountain Product term, but communication strategies and public information provision are needed to enhance consumers' overall knowledge [29,30]. Moreover, these are also attributes considered by mountain tourists, namely regarding the perception of ecosystem services, such as the maintenance of pastures and grazing, biodiversity conservation, and regulation of hydrogeological assets [31].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have delved into the significance of quality seals. Particularly noteworthy is the recent surge in published papers focusing on the MP label within the dairy sector (Staffolani et al, 2022;Stiletto & Trestini, 2022;Zanchini et al, 2023). The studies largely concur that consumers are willing to pay a premium for foods labelled as MPs.…”
Section: Introductionmentioning
confidence: 99%